دور الاستراتيجيّات التّسويقيّة في تحسين الحصّة السّوقيّة للمصارف العاملة في مدينة حماه - زاهر بسّام; حسن نيروز (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدفت هذه الدّراسة إلى تحديد دور الاستراتيجيّات التّسويقيّة في تحسين الحصّة السّوقيّة للمصارف العاملة في مدينة حماه، من خلال بيان دور استراتيجيّة الهجوم، واستراتيجيّة الدّفاع. وقد اعتمدت الباحثة على المقاربة الاستنباطية كمنهج عام للبحث، وإتّباع منهجية المسح، وقامت بتوزيع الاستبيان على 356 فرد من العاملين في المصارف محل الدراسة، وقد خلصت الدراسة إلى وجود علاقة طردية معنوية بين الاستراتيجيّات التّسويقيّة والحصّة السّوقيّة. ثمّ قدّمت ملخّص لأهمّ النتائج الّتي تمّ التوصّل إليها، حيث كانت النتيجة الرئيسة الأهمّ هي إتّباع المصارف محل الدراسة لاستراتيجيّات تسويقيّة قادرة على تحسين الحصّة السّوقيّة، ثمّ تمّ عرض بعض المقترحات والتوصيات لتحسين العلاقة والّتي أهمّها: ضرورة تبني استراتيجيّة الهجوم من خلال التأكيد المستمر على دراسة العملاء بهدف تحسين الحصّة السّوقيّة للمصارف. This study aimed to identify the relationship between the marketing strategies and the market share of banks operating in the city of Hama. By Identifying the role of each the offensive strategy, and defensive strategy. The researcher relied on the Deductive Approach as a general method. She follows a survey methodology, and she gave a questionnaire to 356 people, they are workers in this banks, The main result of the study was that there a positive significant relationship between the marketing strategies and the market share. We have provided a summary of the main result that have found out is that the follow of banks operating in the city of Hama of marketing strategies capable to improve market share. With the presentation of some of the proposals and recommendations to improve the relationship including the continuous confirmation on studying of customers, in order to enhance market share to banks.